IMPACT OF BEAUTY STANDARDS ON THE CHOICE OF COSMETIC PROCEDURES AND THE INCIDENCE OF BODY IMAGE DISORDERS AMONG STUDENTS AT UNIEVANGÉLICA - Silva, Amanda Cabral; Araújo, Ana Vitória de; Lima, Claudinei Sousa (CIPEEX, 2025)
Objective: To investigate how the pursuit of ideal aesthetics affects individuals of different ages, genders, and ethnicities, analyzing the incidence of surgical procedures and other aesthetic behaviors, such as tattoos, and the influence of these factors on self-image perception and the importance of appearance in different relationship contexts. Methodology: The descriptive and cross-sectional study involved 60 students from the Evangelical University of Goiás, from the Architecture and Urbanism, Engineering, and Law programs, using questionnaires on self-image and self-esteem, in addition to anthropometric measurements to assess body satisfaction. Results: The results revealed that 62.8% of participants are between 19 and 20 years old, a critical age group for aesthetic concerns. It was observed that 42.4% considered fat removal, while 74.08% reported the habit of pinching areas with fat accumulation, especially in the abdominal region. The analysis also showed that 70.03% of participants believe that aesthetic pressure persists even in romantic relationships. Conclusion: These data highlight the continuing influence of aesthetic norms on the self-image and behaviors of the individuals studied.